Application of Example Non Example Learning Model in Improving Symbolic Thinking Ability in Group B1 Children at Dewi Kunti II Dalung Kindergarten - Mariana Prisca Fahik; Christiani Endah Poerwati; Elizabeth Prima (Sean Institute, 2025)
It is important for educators to be creative and innovative in implementing the learning process in order to support aspects of children's development. One of them is the ability to think symbolically. The symbolic thinking ability of early childhood needs to get the right stimulation so that it can develop optimally. This study aims to determine the symbolic thinking ability before and after the application of the Example Non-Example learning model in improving children's symbolic thinking ability. This learning method prioritizes the use of concrete and non-concrete examples to help children understand symbolic concepts better. The type of research used is Classroom Action Research by implementing 2 cycles and each cycle consists of 4 stages of planning, implementation, observation, and reflection. Data collection techniques use observation and documentation methods. Analysis of the results of symbolic thinking abilities is carried out quantitatively. The results of the analysis show that the percentage of completeness of children's symbolic thinking abilities in the initial observation was 41.67% in Cycle I reaching 70.83% and Cycle II increasing to 91.7% These results indicate that the application of the Example Non Example learning model can improve symbolic thinking abilities in children in Group B1 of Dewi Kunti II Dalung Kindergarten.